2010
DOI: 10.1051/0004-6361/200912903
|View full text |Cite
|
Sign up to set email alerts
|

Radio counterpart of the lensed submm emission in the cluster MS0451.6-0305: new evidence for the merger scenario

Abstract: Context. SMM J04542-0301 is an extended (∼1 ) submm source located near the core of the cluster MS0451.6-0305. It has been suggested that part of its emission arises from the interaction between a LBG and two EROs at z ∼ 2.9 that are multiply-imaged in the optical/NIR observations. However, the dramatic resolution difference between the sub-mm map and the optical/NIR images make it difficult to confirm this hypothesis. Aims. In a previous paper, we reported the detection of 1.4 GHz continuum radio emission coi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Interestingly, a SCUBA detection of an extended source in the cluster centre led to the identification of an ERO pair, triple imaged (Chapman et al 2002;Takata et al 2003;Berciano Alba et al 2010). These features point towards the bright central galaxy as the centre of the mass distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a SCUBA detection of an extended source in the cluster centre led to the identification of an ERO pair, triple imaged (Chapman et al 2002;Takata et al 2003;Berciano Alba et al 2010). These features point towards the bright central galaxy as the centre of the mass distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Such extreme SFRs likely result from major mergers (e.g. Chapman et al 2004;Swinbank et al 2004;Greve et al 2005;Tacconi et al 2006Tacconi et al , 2008Younger et al 2007Younger et al , 2008Berciano Alba et al 2010;Narayanan et al 2009Narayanan et al , 2010 and cannot be sustained for a long period (after a few hundred Myr at most the gas reservoir should be depleted; see Greve et al 2005;Hainline et al 2006).…”
Section: Star Formation Ratesmentioning
confidence: 99%
“…The galaxy cluster MACS J0454.10300 ( z = 0.538, also known as MS 0451.60305) has been subject to extensive study due to its high X‐ray luminosity, strong SZ effect, and high redshift (e.g. Ellingson et al 1998; Molnar et al 2002; Laroque et al 2003; Geach et al 2006), and is known to host various lensed submillimetre sources with radio counterparts (Takata et al 2003; Borys et al 2004; Berciano Alba et al 2007, 2010), which we incorporate in our analysis below. Previous strong‐lensing models of this cluster were introduced by Borys et al (2004) and Berciano Alba et al (2010) with similar symmetry as our model.…”
Section: Strong‐lensing Modelling and Analysismentioning
confidence: 99%
“…In the case of MACS J1149.5+2223 (Zitrin & Broadhurst 2009), a background spiral galaxy at z = 1.49 (Smith et al 2009) has been shown to be multiply‐lensed into several very large images, requiring a very shallow, unrelaxed central mass distribution. Another large multiply‐lensed submillimetre source at a redshift of z ≃ 2.9 has been identified in MACS J0454.10300 (also referred to as MS 0451.60305; Takata et al 2003; Borys et al 2004; Berciano Alba et al 2007, 2010), MACS J0025.41222 was found to be a ‘bullet cluster’ like (Bradač et al 2008b) and other MACS clusters have been recently used for an extensive arc statistics study (Horesh et al 2010).…”
Section: Introductionmentioning
confidence: 99%